Thermal-assisted pressure processing: effects of marination, temperature, and pressure level on physicochemical, color and textural parameters of Superficial pectoralis beef muscle - Silva Paz, Reynaldo Justino; Sancho, Ana Maria; Vaudagna, Sergio Ramon; Szerman, Natalia (Wiley, 2025)
This study aimed to evaluate the effects of salt addition and different thermal-assisted pressure processing (TAPP) conditions (temperature and pressure levels) on technological, chromatic, and textural parameters and lipid oxidation of Superficial pectoralis beef muscle. A factorial design with three factors was applied: KCl/NaCl marination (marinated samples MS; non-marinated samples, NMS), temperature during high-pressure processing (50, 70°C), and pressure level (0.1, 200, and 300 MPa). All factors affect the water-holding capacity of beef, which is important to ensure both high yields and optimal tenderness and juiciness in the final product. MS treated at 50°C had the highest yield values, regardless of applied pressure level. TAPP modified the color parameter values of raw samples, resulting in brighter and less reddish. After cooking, color differences remained, indicating that this process did not fully reverse the changes induced by TAPP treatments. MS had lower shear force values than NMS. The presence of salts slightly diminished shear force values. A similar texture profile was obtained for NMS treated at 70°C and 300 MPa and MS treated at 50°C and 200 MPa. NMS and MS treated at 70°C and 0.1 MPa had the highest thiobarbituric acid reactive substance values. Based on the results, marinated samples treated at 200 MPa and 50°C were selected for treatment. TAPP could be an innovative technology for the development of value-added beef products with assured texture.